Effects of different warm-up protocols on swim start performance - Durovic, M.; Durovic, M.; Stojanovic, N.; Okicic, T.; Stojiljkovic, N.; Trajkovic, N. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
In competitive swimming, especially in short events swim start performance has a positive influence on the final result (Arellano, Brown, Cappaert & Nelson, 1994). Warm-up strategies could be a significant contributor to performance in swimming (Ðuroviæ, Stojanoviæ, Stojiljkoviæ, Karaula and Okièiæ, 2022). Warm-up intensity, duration and the recovery time between the warm-up and event represent the most important elements on which the final outcome of the race depends (Zochowski, Johnson, Sleivert, 2007). Therefore, it is necessary to apply adequate warm-up protocols to prepare swimmers more efficiently. The recovery period after warm-up should be more than 5 min but less than 15-20 min (Bishop, 2003). The recovery period between 5 and 15-20 min allows an optimal performance after post-activation performance enhancement (PAPE) stimuli (Kilduff, Cunningham, Owen, West, Bracken, & Cook, 2011). Study Zochowski et al. (2007) showed that international swimmers reduce time by 4 s at 200 m swim time after 10 min recovery period compared to the 45 min recovery period, and did not increase blood lactate or heart rate. In practice, it is not possible for swimmers to have a recovery period of 10 minutes before the race after the warm-up because they have to appear in the call room 20 min before the start of the race. Therefore, swimmers do an extra warm-up before the race. PAPE has been described as a very effective method that can significantly contribute to the performance of movements requiring maximal voluntary effort (Cuenca-Fernández, Smith, Jordan, MacIntosh, López-Contreras, Arellano, & Herzog, 2017) as the swim start. Therefore, the aim of the study was to determine the effects of three different warm-up protocols on swim start performance.